Sosialisasi Rancang-Bangun Pembangkit Listrik Skala Kecil Sistem Organic Rankine Cycle (ORC) di Pincara Kabupaten Luwu Utara - Indar Chaerah Gunadin (Faculty of Engineering UNHAS, 2023)
The availability of hot water energy sources in Pincara Village, North Luwu Regency, South Sulawesi Province, is a potential that must be developed as a source of electrical energy for the people in the village and surrounding villages. The existence of cheap energy sources will have an impact on improving the economy for villagers, most of whom make a living as farmers. In line with the development of industrial development in developing countries such as Indonesia where electrical energy is needed in increasing amounts of capacity, conventional sources of power generation (oil/gas) will not meet the required supply. Geothermal is an alternative to renewable energy sources other than biomass, hydro/wind/solar power, sea waves and nuclear power; which may be the main choice as a substitute for conventional/non-renewable energy sources. In connection with the direct use of geothermal energy sources that have low temperatures which are considered uneconomical, from these conditions, a technology is needed that is able to utilize geothermal energy sources that have low temperatures. One of the technological innovations for utilizing geothermal energy that has a low temperature is Organic Rankine Cycles. Organic Rankine Cycle (ORC) which is a modification of the Rankine cycle by using refrigerant as a working fluid to produce electrical energy. This system consists of four main components, namely the evaporator, turbine, condenser, and pump. The working fluid is pumped into the evaporator to generate steam.